Exploring the influence factors and operating mechanisms of age-friendly communities in urban fringe areas from the resilience perspective: a case study in Shangjie Township, Southeast China - Pinqi Wu; Haiying Liu; Yafeng Zou; Chengfeng Yi; Pingping Du; Yan Song (Frontiers in Public Health, 2025)
IntroductionThe development of age-friendly communities (AFC) is a key initiative in response to the active ageing strategy proposed by World Health Organization. Urban fringe communities (UFC) are characterized by distinctive features such as intricate built environments and heterogeneous resident populations, and these characteristics pose a great challenge to the promotion of age-friendliness in these areas.MethodsThis study combines field surveys and spatial analysis to reveal the age-friendliness in different types of UFC in Shangjie Township, southeastern China. And we employ structural equation model to quantitatively analyze the factors influencing age-friendliness in these communities. Then, this study proposes a mechanism for the operation of AFC in UFA based on the DPSIR model.ResultsOver 50% of the UFC in the study area exhibit satisfactory age-friendliness, while the age-friendliness in some communities still requires urgent improvement. Furthermore, community space, facilities and services, social interactions, and social participation all positively influence the age-friendliness of UFC, with effect sizes ranked in descending order as follows: facilities and services, social interactions, social participation, and community space.DiscussionThis study develops a systematic framework for enhancing the age-friendliness of UFC, providing a viable strategy for addressing the challenges of population ageing. The findings of this study make both theoretical and practical contribution to the development of AFC in UFA.